2016
DOI: 10.1038/srep35660
|View full text |Cite
|
Sign up to set email alerts
|

AKT/GSK3β signaling pathway is critically involved in human pluripotent stem cell survival

Abstract: Human embryonic and induced pluripotent stem cells are self-renewing pluripotent stem cells (PSC) that can differentiate into a wide range of specialized cells. Basic fibroblast growth factor is essential for PSC survival, stemness and self-renewal. PI3K/AKT pathway regulates cell viability and apoptosis in many cell types. Although it has been demonstrated that PI3K/AKT activation by bFGF is relevant for PSC stemness maintenance its role on PSC survival remains elusive. In this study we explored the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 55 publications
2
55
0
1
Order By: Relevance
“…As shown in Figure 1, combined database analysis of differentially expressed genes suggests enrichment of FGF (signaling by FGFR2 mutants), WNT (negative regulation of T cell factor-dependent [TFC-depen signaling is implicated in the induction of pluripotent stem cells (9)(10)(11)(12). Moreover, when expression of dysregulated genes was filtered to detect genes specifically involved in signal transduction, enrichment of genes involved in cell cycle progression and stem cell pluripotency signaling was observed (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1, combined database analysis of differentially expressed genes suggests enrichment of FGF (signaling by FGFR2 mutants), WNT (negative regulation of T cell factor-dependent [TFC-depen signaling is implicated in the induction of pluripotent stem cells (9)(10)(11)(12). Moreover, when expression of dysregulated genes was filtered to detect genes specifically involved in signal transduction, enrichment of genes involved in cell cycle progression and stem cell pluripotency signaling was observed (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Network analysis of these pathways revealed a high degree of cross-talk, denoted by 112 nodes sharing 372 edges, suggesting a high degree of cooperation between mechanisms of signal transduction ( Figure 1C). Interestingly, the combined activation of Notch, WNT, and FGF signaling is implicated in the induction of pluripotent stem cells (9)(10)(11)(12).…”
Section: Resultsmentioning
confidence: 99%
“…GSK-3β activates caspase-3 and leads to apoptotic cell death. Activated Akt inhibits GSK-3β function and mediates anti-apoptotic effect [23]. Previous studies reported that resveratrol improves neurological behavior score and attenuates brain damage on ischemic stroke [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Protein kinase B (PKB, also known as Akt) plays a significant role in various cellular functions such as cell survival, proliferation and metabolism (11). The phosphorylation of Akt at serine 473 is known to regulate Glycogen Synthase kinase-3β (GSK-3β) inactivation through phosphorylation of GSK-3β at serine 9 (12). GSK-3β is one of the two GSK-3 isoforms, and it regulates cell growth, differentiation and cell survival (13).…”
Section: Introductionmentioning
confidence: 99%